1991
DOI: 10.1093/oxfordjournals.aje.a115818
|View full text |Cite
|
Sign up to set email alerts
|

Hair Dye Use and Breast Cancer: a Case-Control Study among Screening Participants

Abstract: To investigate whether hair dye use increases the risk of breast cancer, a case-control study was conducted among patients attending a screening center in New York City. The study group consisted of 398 breast cancer cases identified at the screening center between 1977 and 1981, and 790 randomly selected controls screened during the same period. Subjects were interviewed by telephone to obtain information on known risk factors for breast cancer, along with a complete history of hair dye use detailing type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…The results from the large, prospective ACS study (7), conducted by Thun et al, offer reassuring evidence. Taken together with results from other studies (2)(3)(4), these data suggest that we must turn to other lifestyle factors to account for changes in cancer mortality among women over time. This study (7) is of sufficient size (over half a million women followed for more than 6 years, during which 9435 cancer deaths were confirmed) that the investigators are also able to examine relations with specific cancers.…”
supporting
confidence: 71%
“…The results from the large, prospective ACS study (7), conducted by Thun et al, offer reassuring evidence. Taken together with results from other studies (2)(3)(4), these data suggest that we must turn to other lifestyle factors to account for changes in cancer mortality among women over time. This study (7) is of sufficient size (over half a million women followed for more than 6 years, during which 9435 cancer deaths were confirmed) that the investigators are also able to examine relations with specific cancers.…”
supporting
confidence: 71%
“…Excluding cohort studies that relied on PMR or mortality odds ratio (MOR) analyses, the median number of women included in these studies was about 1500: 18 studies included more than 5000 subjects, and six studies included more than 10 000 subjects.73 77 80 96 134 135 153 154 The median number of breast cancer cases was 19 (mean of 64), and only five studies had more than 100 cases. 75 Table 3 continued overleaf statistical power was above 80% in about 75% of studies, the small number of cases found indicates that the power to detect excess risks in subgroups and to test for trends in exposure was generally low.…”
mentioning
confidence: 99%
“…A total of 11 case-control studies (7,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and four cohort studies (16,(18)(19)(20)35) have investigated the relationship between personal hair dye use and risk of breast cancer (Table 2). Nearly all of the studies have yet to suggest a conclusive no association between breast cancer risk and exposure to hair dyes with the exception of one case-control study (34).…”
Section: Breast Cancermentioning
confidence: 99%
“…No association between breast cancer and hair dye use was noted in most case-control studies (7,(24)(25)(26)(28)(29)(30)(31)(32)(33). When some of these studies estimated frequency, duration, or dose-response relationships, no significant results exists for most studies.…”
Section: Breast Cancermentioning
confidence: 99%